The experiences of patients not conveyed after evaluation by emergency medical services in Southwest Finland – A qualitative survey study - Kuoppala, Anne (Elsevier, 2025)
Background: The amount of non-critical Emergency Medical Services missions has been increasing. After examination and treatment, paramedics can decide, based on guidelines, not to convey the patient to a healthcare facility. This study aimed to investigate patients' experiences in non-conveyance situations in Southwest Finland. Our research questions were: 1) Which patient concerns were not addressed? 2) What key actions improved patient comfort? and 3) What possible enhancements could make the patient experience more positive?
Methods: This was a qualitative survey study. In March 2023, all the patients who met the inclusion criteria (N = 1017) received a survey via mail. The data from three open-ended questions were analyzed using inductive content analysis.
Results: The response rate was 22.2 % (n = 226). The unaddressed patient concerns were related to inadequate immediate care and guidance and non-clinical factors causing concern. Key actions for improved patient comfort were related to immediate treatment and guidance, as well as non-clinical factors that impact the patient experience. More thorough treatment processes and more attentive encounters would have enhanced the patient experience.
Conclusions: Predominantly, patients reported having received excellent services. Utilizing paramedics' soft skills and keeping the patient as the central focus is key to improving the non-conveyance process and experience.